Illocutionary acts reveal literary conflict between black and white american in the dear white people movie - Rita Hartati; David Joshua Adrian (Cendikia : Media Jurnal Ilmiah Pendidikan, 2023)
Background: This study investigates illocutionary acts used by characters in Dear White People Movie  Reveal Literary Conflict between Black and White American. A drama is work of literature and it is more than the presentation human life. The theory of illocutionary act is chosen because it is used to describe how speaker should communicate something to hearer. The researcher chooses this drama because after reading the text there are kinds of illocutionary acts. The objectives of this research is to identify the types of illocutionary act used by the main characters and explain the meaning and its types of illocutionary act reveal literary conflict represented the conflict between black and white American in Dear White People movie. The research will be conducted by using descriptive qualitative method. The data of this research are speech act of  illocutionary act of reveal racism conflict from the characters’ dialog or conversation. The conclusions of this research are There are some illocutionary acts found in Dear White People movie, such as: expressives and representatives. The most using illocutionary acts is representatives. The racism in the movie Dear White People is not dissapear. The racism in this film is in the form of the regulation of housing replacement for student of Winchester.